Effect of Surface and Bulk Properties of Mesoporous Carbons on the Electrochemical Behavior of GOx-Nanocomposites - Garcia-Perez, Tsai; Hu, Shouzhen; Wee, Youngho; Scudiero, Louis; Hoffstater, Conrad; Kim, Jungbae; Ha, Su (Frontiers in Chemistry, 2019)
Biofuel cell (BFC) electrodes are typically manufactured by combining enzymes that act as catalysts with conductive carbon nanomaterials in a form of enzyme-nanocomposite. However, a little attention has been paid to effects of the carbon nanomaterials’ structural properties on the electrochemical performances of the enzyme-nanocomposites. This work aims at studying the effects of surface and bulk properties of carbon nanomaterials with different degrees of graphitization on the electrochemical performances of glucose oxidase (GOx)-nanocomposites produced by immobilizing GOx within a network of carbon nanopaticles. Two types of carbon nanomaterials were used: graphitized mesoporous carbon (GMC) and purified mesoporous carbon (PMC). Graphitization index, surface functional groups, hydrophobic properties, and rate of aggregation were measured for as-received and acid-treated GMC and PMC samples by using Raman spectrometry, X-ray photoelectron spectroscopy (XPS), contact angle measurement, and dynamic light scattering, respectively. In addition to these physical property characterizations, the enzyme loading and electrochemical performances of the GOx-nanocomposites were studied via elemental analysis and cyclic voltammetry tests, respectively. We also fabricated BFCs using our GOx-nanocomposite materials as the enzyme anodes, and tested their performances by obtaining current-voltage (IV) plots. Our findings suggest that the electrochemical performance of GOx-nanocomposite material is determined by the combined effects of graphitization index, electrical conductivity and surface chemistry of carbon nanomaterials.